2011
DOI: 10.1007/s12072-011-9265-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum hepatitis B virus DNA before liver transplantation correlates with HBV reinfection rate even under successful low-dose hepatitis B immunoglobulin prophylaxis

Abstract: PurposeThe combination of hepatitis B immunoglobulin (HBIg) and nucleos(t)ide analogues has been accepted as the best treatment to control hepatitis B recurrence after orthotopic liver transplantation (OLT). However, the optimal dose of HBIg remains unclear. We have previously reported that high-dose HBIg in the early period followed by low-dose HBIg with nucleos(t)ide analogues offers reliable and cost-effective control of hepatitis B recurrence. The aim of this study was to investigate intrahepatic hepatitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…This observation has also been reported in several other studies. Yasunaka et al [37] evaluated disease recurrence following LT for HBV-related liver disease and concluded that serum HBV DNA before LT correlated with the HBV reinfection rate even with the successful administration of low-dose HBIG prophylaxis. Thirty-two (24%) of our patients experienced HBV/HDV coinfection.…”
Section: Discussionmentioning
confidence: 99%
“…This observation has also been reported in several other studies. Yasunaka et al [37] evaluated disease recurrence following LT for HBV-related liver disease and concluded that serum HBV DNA before LT correlated with the HBV reinfection rate even with the successful administration of low-dose HBIG prophylaxis. Thirty-two (24%) of our patients experienced HBV/HDV coinfection.…”
Section: Discussionmentioning
confidence: 99%
“…To protect against HBV infection of naïve hepatocytes might be difficult, since recent studies have revealed that intrahepatic HBV-DNA is detectable in >50% of even well-controlled patients after OLT [5]. The HBV virion released from the infected cells could be blocked with anti-HBs antibody.…”
Section: Immune Responses In Post-olt Hbv Recurrence Controlmentioning
confidence: 99%
“…Advanced molecular methods can now be used to identify HBV genomic elements in hepatocytes, such as HBV total DNA and covalently closed circular DNA (cccDNA) 4. The presence of total DNA and cccDNA identifies grafts with the potential for viral replication.…”
Section: Hbvmentioning
confidence: 99%